RETRACTED: 20-HETE Inhibition by HET0016 Decreases the Blood–Brain Barrier Permeability and Brain Edema After Traumatic Brain Injury - Lu, Liyan; Wang, Mingliang; Wei, Xiaoer; Li, Wenbin (Frontiers in Aging Neuroscience, 2018)
Recent studies have implicated 20-HETE as a vasoconstrictive mediator in trauma, the purpose of this study was to determine wheter administration of HET0016, the 20-HETE inhibitor, could protect neurons from trauma and the effect of HET0016 on the blood brain barrier (BBB) and brain edema in experi-mental traumatic brain injury. Rat models with traumatic brain injury were es-tablished. Brain edema was measured according to the wet and dry weight me-thod at 3 h, 24 h and 72 h after injury. The BBB permeability was quantified by dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). Superox-ide production, the activity of superoxide dismutase (SOD) and total antioxida-tive capability (T-AOC) in traumatic brain tissues were also measured. Western blot analysis was used to analyze the expression of the occludin, ZO-1, MMP-9, and JNK pathways. At 24 h and 72 h after administration of HET0016 following TBI, the BBB permeability and brain edema decreased. The decrease in supe-roxide production and the increase in the activity of SOD and T-AOC were measured in this study. Western blot analysis showed that the expression of MMP-9 and JNK pathways was suppressed, but the expression of ZO-1 and oc-cludin was increased. These results suggest that the administration of HET0016 could protect the BBB function and decrease brain edema after experimental traumatic injury by suppressing the expression of MMP-9 and activating the ex-pression of tight junction proteins via suppressing the JNK pathway and oxida-tive stress.